Business Ethics in Islamic Finance - Mathkur, Naif Mansour M. (Archives of Business Research, 2019)
The goal of this research undertaking is to provide illuminating insights on the phenomenon of business ethics in Islamic finance. The paper offers insight into the ways that Islamic finance can enhance the upholding of utmost business ethics in diverse settings. For this, the study employees a meticulous literature review that covers an array of credible primary, secondary, and tertiary sources. This research dissemination finds that many players in the Islamic finance segment observe business ethics in general. Scores of Islamic finance practitioners observe the business ethics laid out in the Shari’ah. However, there are quite a few notable cases of wayward participants who have not been true to business ethics. The results of deviation from ethical business practices have been catastrophic. To deepen the observance of business ethics, it is important for the Islamic finance industry to deploy pragmatic and objective models that can be timely applied to warn of possible deviation from the observance of the ethical ideals laid out in the Shari’ah and avert the possible adverse consequences. The paper is tentative in nature. There is a need for further empirical research.